2012
DOI: 10.1002/polb.23216
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylidene fluoride‐co‐chlorotrifluoroethylene and polyvinylidene fluoride‐co‐hexafluoropropylene nanofiber‐coated polypropylene microporous battery separator membranes

Abstract: Nanofiber-coated polypropylene (PP) separator membranes were prepared by coating a Celgard V R microporous PP membrane with electrospun polyvinylidene fluorideco-chlorotrifluoroethylene (PVDF-co-CTFE) and PVDF-co-CTFE/ polyvinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP) nanofibers. Three PVDF polymer solutions of varying compositions were used in the preparation of the nanofiber coatings. Two of the polymer solutions were PVDF-co-CTFE blends made using different types of PVDF-co-HFP copolymers. The PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The fibrous structure of the PAN membrane plays a key role in its ion transport and conductivity behavior. 39 The electrolyte uptake results shown in Figure 3(a), showed that the PAN membrane has a large mass electrolyte uptake of about 328% compared to the PP Celgard separator value of 82%. Factors such as viscosity, surface tension, solution concentration had a direct influence on the fiber diameters of the Forcespun V R fibers; however, the effect of these factors were minimized through heating of the solution in the silicon oil bath, choosing the appropriate needle gauge (i.e., 30Gx 1 = 2 00 ), and the spinneret speed.…”
Section: Separator Morphologymentioning
confidence: 98%
See 2 more Smart Citations
“…The fibrous structure of the PAN membrane plays a key role in its ion transport and conductivity behavior. 39 The electrolyte uptake results shown in Figure 3(a), showed that the PAN membrane has a large mass electrolyte uptake of about 328% compared to the PP Celgard separator value of 82%. Factors such as viscosity, surface tension, solution concentration had a direct influence on the fiber diameters of the Forcespun V R fibers; however, the effect of these factors were minimized through heating of the solution in the silicon oil bath, choosing the appropriate needle gauge (i.e., 30Gx 1 = 2 00 ), and the spinneret speed.…”
Section: Separator Morphologymentioning
confidence: 98%
“…[36][37][38][39] To further elucidate, the effects of membrane microstructural properties like; porosity, pore size and thickness on the electrolyte capacity, future experiments will be designed to investigate the effect of Forcespun polymer and nanocomposite membranes on these microstructural properties with the aim to improve the separator performance, mechanical strength, thermal, and shutdown properties. The electrolyte uptake, which is a measure of the amount of liquid electrolyte absorbed per unit area of the membrane, is one key performance index of a good lithium ion battery separator.…”
Section: Separator Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…8,[11][12][13] Recently, several strategies have been proposed to improve the electrolyte wettability of polyolefin separators including physical coating and chemical modification. [14][15][16] For example, Lee et al coated polypropylene (PP) separators with polyvinylidene fluoride (PVDF) copolymer nanofiber using electrospinning technology, which largely improved the electrolyte wettability and the corresponding electrochemical performance of LIBs. 14 However, the physical coating layers are normally unstable in the electrolyte, which could easily delaminate from the separator.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudo‐block structure of PVDF‐CTFE offers feasibility for possible grafting modification via atom transfer radical polymerization (ATRP) preserving the high mechanical, thermal, and chemical stabilities . Intense research efforts are underway on the use of the materials for electrical energy storage, as high energy materials, and the development of gel electrolyte membranes. In particular, its key features for energy storage application are its high ionic conductivity and good compatibility with lithium metal electrodes …”
Section: Introductionmentioning
confidence: 99%